Rubber hand pollination in Indonesian Rubber Research Institute program currently uses Wickham population which genetic analysis showed that genetic diversity of this population is narrow. The development of breeding activity has made the genetic base narrower by inbreeding. In order to solve this problem can use a new genetic resource that is the rubber germplasm IRRDB 1981 population. The genetic relationship between these populations is important to choose parents to avoid closely related gen - FETRINA OKTAVIA; MUDJI LASMININGSIH; . KUSWANHADI (Bogor Agricultural University, Indonesia, 2011)
Rubber hand pollination in Indonesian Rubber Research Institute program currently uses Wickham population which genetic analysis showed that genetic diversity of this population is narrow. The development of breeding activity has made the genetic base narrower by inbreeding. In order to solve this problem can use a new genetic resource that is the rubber germplasm IRRDB 1981 population. The genetic relationship between these populations is important to choose parents to avoid closely related genotypes in hand pollination. Therefore RAPD analysis was carried out using four selected primers i.e. OPH-03, OPH-05, OPH-18 and OPN-06. The result showed that Wickham and IRRDB 1981 population were separated into two different big groups with genetic similarity value of 0.64, and those big groups were separated further into many small sub groups with some genetic similarity level. The genetic similarity matrix showed that Wickham and IRRDB 1981 population has a range of genetic similarity 0.37– 0.98. The highest genetic similarity was found between RRIM 600 and PN 621, while the lowest was between BPM 1 and RRIC 100. Value in this matrix showed the genetic diversity between each clone. Based on this result, rubber genotypes of Wickham population could be crossed with genotypes of IRRDB 1981 population by choosing genotypes that have low genetic similarity.